Expert Review of Cervical Cytology: Does it Affect Patient Care?. Issue 2 (April 2018) - Mark, Jaron; Morrell, Kayla; Eng, Kevin; Alfiero, Alexandra; Frederick, Peter J.
Abstract : Objectives: The aim of the study was to evaluate whether expert review of outside cervical cytology affects patient care. Materials and Methods: A retrospective study was conducted of 424 new patient referrals for cervical dysplasia between 2004 and 2016 at Roswell Park Cancer Institute. Records were analyzed for outside cervical cytology reports and compared with expert cervical cytology review. Differences between expert review and outside reports were documented. Charts with a difference were then assessed for additional evaluation and procedures performed. We specifically analyzed the data for cytology being upgraded or downgraded after expert review. Results: Two hundred forty-six patient charts were eligible for this study. We identified 165 patients with congruent pathology reports. Of the 81 different reports, 41 led to significant pathologic differences. Twenty-four reports with different pathology were low-grade squamous intraepithelial lesions (LSIL) upgraded to high-grade squamous intraepithelial lesions (HSIL). Six were HSIL downgraded to LSIL, 4 LSIL downgraded to negative, 3 AGC upgraded to HSIL, 2 AGC upgraded to cancer, 1 each for HSIL downgraded to negative, and AGC downgraded to negative. Of the 24 patients whose cytology changed from low grade to high grade, 17 underwent an excisional procedure and 1 had a laser ablative procedure. Cervical intraepithelial neoplasia 2 or 3 was found in 11 specimens. Cervical intraepithelial neoplasia 1 was found in 4 of excisional specimens and no dysplasia found in 2. Conclusions: Expert review of cervical cytology significantly impacts patient management at a tertiary referral center, resulting in both upgrading and downgrading of community cytology reports.